Culture of Microalgae from Sewage Effluent. Issue 12 (15th October 2013) - Inoue, K.; Uchida, T.
Abstract Microalgae were cultured using actual sewage effluent and the influences of various controls such as the hydraulic retention time to the culture were examined. The microalgae could be cultured by supplying only sewage effluent without additional external microalgal stock or nutrient salts. As the microalgae increased, the nutrient salts and metals were removed from the culture water. The cell number of green algae increased to 3.3 times by increasing the hydraulic retention time from 4 d to 6 d. With the addition of air into the culture water, the green algae accounted for 87 % of the total population. These controls led to an increase in the useful green algae components as the fuel.